Characteristics of Asymptomatic Bacteriuria in Diabetes Mellitus Patients: A Retrospective Observational Study - Asghar, Muhammad Sohaib (Cureus, 2021)
Background and objective The term asymptomatic bacteriuria (ASB) refers to the isolation of bacteria in a urine specimen of individuals without any symptoms of urinary tract infection (UTI). Diabetes mellitus (DM) is a disease involving multiple organ systems, characterized by its chronicity and hence endless complications including ASB. This study aimed to determine the characteristics of ASB and antibiotic susceptibility patterns among patients with diabetes. Materials and methods This was a retrospective observational study conducted in a tertiary care hospital. The study included patients with a diagnosis of diabetes with no signs and symptoms of UTI but who still showed the growth of an organism in urine culture. A total of 222 urine cultures were analyzed retrospectively, ensuring that they met the inclusion criteria through non-probability consecutive sampling. Results The mean age of the study participants was 62.89 ± 13.77 years; 76% of them were females, and 61% had a family history of diabetes. The most frequent organisms isolated were Escherichia coli (E. coli), Enterococcus, Klebsiella pneumonia, Pseudomonas aeruginosa, and Enterobacter species. A total of 20 subjects had dual bacterial growth in their cultures, with Enterococcus species (n=17) being the most common organism. Gender, family history of diabetes, levels of hemoglobin A1c (HbA1c), and advanced age were all found significantly associated with ASB. Conclusion Our study is the first of its kind to analyze and examine the risk factors associated with ASB in DM patients, and to identify the pathogens involved, along with assessing their antibiotic resistance profiles.